Surface Electric Potential Measurement with a Static Probe - R. I. Vorobey; O. K. Gusev; A. I. Zharin; V. A. Mikitsevich; K. U. Pantsialeyeu; A. V. Samarina; A. I. Svistun; A. K. Tyavlovsky; K. L. Tyavlovsky (Приборы и методы измерений, 2023)
Surface electric potential measurements are widely used in non-destructive inspection and testing of precision surfaces, for example, in the production of semiconductor devices and integrated circuits. Features of the construction and application of devices for measuring the surface electric potential using an immovable reference electrode are considered. Despite the need to increase the area of the probe compared to devices with a vibrating probe, measurement techniques with an immovable probe have a number of advantages and could expand the scope of surface electric potential measurements in the inspection of samples with precise surfaces. Models of the formation of a measuring signal in the presence of a spatial inhomogeneity of surface electric potential are presented and discussed.